Analisis Financial Sustainability dengan Size Sebagai Moderasi Pada Sektor Keuangan yang Terdaftar di BEI - Jennifer, Jennifer; Tanto, Tanto (Forum Kerjasama Pendidikan Tinggi, 2025)
Banking financial sustainability is a vital indicator in maintaining the stability of the national financial system, especially amid global economic dynamics. This study investigates the effect of BOPO, NIM, and LDR on the Financial Sustainability Ratio (FSR) by taking into account bank size as a moderating variable. This study focuses on 33 banks listed on the Indonesia Stock Exchange (IDX) that consistently recorded profits during the 2020–2024 period, resulting in 165 annual observations. Secondary data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) assisted by SPSS 26. The results show that BOPO produces a significance value of 0.000<0.05, which has a significant negative effect on FSR, NIM with a significance value of 0.000<0.05, which has a significant positive effect, while LDR with a significant result of 0.195>0.05, which means that LDR has no effect. Size was proven to moderate the relationship between BOPO, NIM, and LDR with FSR, where the significance results of BOPO 0.011, NIM 0.014, and LDR 0.000 were smaller than 0.05, indicating that the operational scale can strengthen or weaken the influence of core financial variables on sustainability. These findings reinforce that cost efficiency, interest income optimization, and asset capacity are strategic synergies in maintaining long-term financial sustainability.